A Research on the Impact of Collaborative Governance in Urban Communities on Building Resilient Cities - Huang Yuxi; Wang Kun (Dealings Foundation Institute, 2025)
Under the influence of various factors, including China’s deepening political reform, the continuous development of the Internet era, and the need to address social pain points, the continuous improvement of urban community management concepts and capabilities is a fundamental way to achieve long-term social stability and development. From the perspective of “collaborative governance” and “building resilient cities” in urban communities, this paper reveals the intrinsic connection between the two. On this basis, using a “trinity” perspective, the management objects of urban social cooperation are divided into three categories: “government, companies, and social organizations.” Through research on urban community management mechanisms, this paper identifies three aspects closely related to building resilient cities in China’s urban community management: government supervision, company capabilities, and social organization participation. To this end, this paper proposes three improvement strategies. First, establish a government supervision mechanism and strengthen the accountability of the main parties. Second, develop the safety cooperation capabilities of regional companies and enhance their self-esteem. Third, encourage social organizations to participate and fully develop their group social skills. This study provides a reference for improving the governance capabilities and modernizing the governance level of urban communities in China.